Fostering toleration in secondary school students through Enlightenment philosophical tales - Matt Sharpe (Journal of Philosophy in Schools)
This paper argues that teachers of philosophy in school, interested in the use of literature in their classrooms, can benefit from teaching the wonderful, but today widely-neglected, literary works of the Enlightenment philosophes. As we examine in Part 1: Theory, these works of philosophical literature were written to reach a large reading public, and engage nonexpert audiences who, like our secondary students, were not necessarily otherwise interested in philosophical questioning. In particular, Enlightenment philosophical literature served to advocate to the reading public the value of religious toleration, and its epistemic preconditions, in forms of intellectual humility. These texts, we argue, are thereby perfect for classroom use in philosophy in schools. In Part 2: Exemplifications, we look at how, in Montesquieu’s Persian Letters and Voltaire’s Micromégas, literary conceits are used to open readers’ eyes to how the ideas and customs they take for granted must appear very differently to others, and how these ‘others’ whom they might have previously disregarded share a good deal with ‘us’, and may even have things to teach us. Such an ‘expanded’ enlightened mindset as these texts foster through engaging readers in their stories and comedy, we propose, remains at the heart of educating our students to be good citizens in multi-faith, post-Enlightenment societies.